Sakral dan Profan dalam Ritual Life Cycle : Memperbincangkan Fungsionalisme Emile Durkheim - Asliah Zainal (Institut Agama Islam Negeri Kendari, 2014)
AbstractIn various societies, ritual manifest in almost all stages of humanlife. It starts from the conception period; birth, childhood,marriage, death, even after the man was die. With the ritual, peopletry to bring the world and at the same time separate the sacred andthe profane one. This paper shall discuss the life cycle rituals insociety in Emile Durkheim’s theory of functionalism. In Durkheim’spoint of view, society has two sides in their life; time to work andtime celebrate the sacred ritual. The dualism of life is whatDurkheim called